2015
DOI: 10.1016/j.wear.2014.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Fiber type effect on tribological behavior when cutting natural fiber reinforced plastics

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractRecently, natural fiber reinforced plastic (NFRP) materials are becoming a viable alternative to synthetic fiber in many industrial applications which not require high structural performances. However, machining of NFRP such as milling process is almost unavoidable operation to facilitate the parts assembly in addition to the finishing of final product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 44 publications
1
76
0
Order By: Relevance
“…Nonetheless, it must be noted that natural fibre; such as flax, should behave differently to that of synthetic fibre. According to Chegdani et al [34], natural fibres are soft by nature due to their high cellulose content. This characteristic gives them the ability to deform under the fibre-tool interaction and limit any failure due to the fibre brittle fracture [34].…”
Section: Experimental Results On Residual Tensile Strength and Delamimentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it must be noted that natural fibre; such as flax, should behave differently to that of synthetic fibre. According to Chegdani et al [34], natural fibres are soft by nature due to their high cellulose content. This characteristic gives them the ability to deform under the fibre-tool interaction and limit any failure due to the fibre brittle fracture [34].…”
Section: Experimental Results On Residual Tensile Strength and Delamimentioning
confidence: 99%
“…According to Chegdani et al [34], natural fibres are soft by nature due to their high cellulose content. This characteristic gives them the ability to deform under the fibre-tool interaction and limit any failure due to the fibre brittle fracture [34]. While this explains the contradictory results of the entrance and exit delamination factor observed in this current study, further investigation could be undertaken through the adjusted delamination factor as suggested by Rubio et al [30] and Davim et al [35].…”
Section: Experimental Results On Residual Tensile Strength and Delamimentioning
confidence: 99%
“…In order to understand the effect of tool coating on the cutting mechanisms of flax fibers inside the NFRP, the specific cutting energy was calculated from cutting forces [28] for each cutting test configuration. Fig.…”
Section: Natural Fiber Cutting Mechanismsmentioning
confidence: 99%
“…However, standard surface A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 roughness reveals a similar behavior between GFRP and NFRP that include high natural fiber stiffness [20]. Thus, previous work of the authors [28] addressed the multiscale influence of the natural fiber type (particularly the fiber stiffness) on the tribological behavior of NFRP during profile milling process. This study showed that the effect of fiber type is more relevant at fiber bundle scales and the machined surface roughness level decreases linearly by fiber stiffness increasing at this scales range.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation